Long-term variations of the sea level on the western coast of the Antarctic Peninsula - V. Maderich; K. Terletska; I. Brovchenko; D. Pishniak (Ukrainian Antarctic Journal, 2019)
The aim of the study is to analyze seasonal and interannual changes in sea level on the western coast of the Antarctic Peninsula. Objects of study are seasonal and interannual variability of sea level, air temperature, pressure at sea level, precipitation in the period 1960–2018 at the Faraday/Akademik Vernadsky station, which was considered as representative site for the Antarctic Peninsula. Statistical methods of study were used, including estimates of linear trends of time series using the nonparametric Sen’s estimator of slope. The Mann-Kendall test was used to assess the significance of the slope of the trend. Time variability analysis was performed using wavelet analysis. Using the MATrix LABoratory (MATLAB) software package, squared of wavelet coefficients were calculated depending on the scale and shift or scalograms that characterize the local energy spectrum, and scalegrams calculated by averaging the scalograms by time shifts. The Morlet wavelet transformations were used. The results of the calculations showed that the trend of sea level at the Faraday/ Akademik Vernadsky station in the period 1960—2018, according to observations and correction on glacial isostatic adjustment of the crust is in the range from 3.05 to 3.45 mm/year, which is significantly higher than the global trend of 2.1 mm/year. Sea level scalograms allow estimating time-averaged periods and amplitudes of the coefficients for each season. In the austral winter and spring characteristic periods were 4—6 years, whereas the summer and autumn periods are characterized by 6–8 years, as well as by the highest amplitudes of the coefficients. All seasons are characterized by the appearance of a weakly pronounced period of about 4 years. The presence of peaks in the scalegrams at 6–8 and 3–4 years confirms the relationship of atmospheric and oceanic processes in West Antarctica to the natural variations of the ocean-atmosphere system, such as the Southern Annular Mode and El Niño-Southern Oscillation, which varies with typical 3–4 and 6–8 year periods. It was concluded that, unlike air temperature, the sea level trend is relatively weakly depends on the season, with the exception of autumn, when sea level trend is three times smaller than the average value. At the same time, the air temperature trend is the largest in the austral winter and the lowest in the summer.